Flexible germanium devices for various applications in internet of things ERA - Kriswind Singh Gill (Nanyang Technological University, 2023)
Developing semiconductor devices is important for technology to evolve. Continuing to attain the most productivity while being power efficient is one of the main goals in the semiconductor industry. In this report, we will focus on the capability and restrictions of flexible Nanomembranes by conducting Raman Spectroscopy and Current-Voltage Measurements.